Cultivated building materials industrialized natural resources for architecture and construction - Hebel, Dirk; Heisel, Felix (Cultivated building materials, 2017)
"The 21st century will face a radical paradigm change in how we produce construction materials--a shift towards cultivating, breeding, raising, farming, or growing future resources. The book presents new industrialized production methods and innovative cultivated building materials, like cement grown by bacteria, bricks made of mushroom mycelium or bamboo fibers as reinforcement for concrete. Aiming to build a bridge from scientific research to product development and application, the book describes the contribution of a wide range of professionals and innovators."--Provided by publisher.